STRATEGI BAITU AL-MÁL DALAM PENGELOLAAN ZAKAT MÁL UNTUK PEMBERDAYAAN MASYARAKAT MUSLIM DI KECAMATAN SEI BAMBAN - Ramadhan Syahmedi Siregar, Sarwedi Gultom, Nawir Yuslem, (Program Pascasarjana UIN Sumatera Utara Medan, 2017)
Abstact: The purpose of this research is to find out how are thestrategy of Baitū al-mal the sub-regency Sei Bamban inmanaging zakat, infaq, and shadaqah to collect and distributezakat fund, infaq, and shadaqah from muzakki for the moslemcivil by Islam law perspective. This research used thequalitative method. This research was placed at the subregencyof Sei bamban. The technique for the data collectingused the documentation, interview and observation. Thetechnique for data collecting used data reduction, dataavailable and conclusion. The source data used for usingprimary source and secondary source. The research showedthe strategy are; a) the collecting and distribution of zakat,infaq, and shadaqah from muzakki by baitu al-m